Simulation of Fuzzy Logic Implementation in an IoT-Enabled Water Quality Monitoring System Using ESP8266 - Jaya, Indra; Nawawi, Muhammad; Hayati; Naila Eka Fazlin (PTE FTK UIN Ar-Raniry, 2026)
This research developed a water quality monitoring system using fuzzy logic and an ESP8266 microcontroller with temperature, humidity, pH, and Total Dissolved Solids (TDS) sensors. The system processes data in real time by converting sensor values ​​into linguistic categories, then produces water quality that meets WHO standards. The system is also connected to an IoT platform to facilitate remote monitoring. Simulation results show that the system is able to recognize overlapping water conditions, for example, at pH 7.5 which falls into the